2007
DOI: 10.1038/nn1997
|View full text |Cite
|
Sign up to set email alerts
|

Microglia: active sensor and versatile effector cells in the normal and pathologic brain

Abstract: Microglial cells constitute the resident macrophage population of the CNS. Recent in vivo studies have shown that microglia carry out active tissue scanning, which challenges the traditional notion of 'resting' microglia in the normal brain. Transformation of microglia to reactive states in response to pathology has been known for decades as microglial activation, but seems to be more diverse and dynamic than ever anticipated--in both transcriptional and nontranscriptional features and functional consequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
2,764
1
44

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,202 publications
(2,853 citation statements)
references
References 99 publications
44
2,764
1
44
Order By: Relevance
“…The function of this interaction between apoE and LRP1, has been associated with suppression of neuroinflammation 57. Microglial cells, which expresses LRP1, are resident macrophages within the CNS that become activated in pathological situations, including cerebral ischemia 58. Microglial activation results in oxidative stress and the release of inflammatory mediators, contributing to BBB breakdown, secondary neuronal injury, and development of cerebral edema 59.…”
Section: Discussionmentioning
confidence: 99%
“…The function of this interaction between apoE and LRP1, has been associated with suppression of neuroinflammation 57. Microglial cells, which expresses LRP1, are resident macrophages within the CNS that become activated in pathological situations, including cerebral ischemia 58. Microglial activation results in oxidative stress and the release of inflammatory mediators, contributing to BBB breakdown, secondary neuronal injury, and development of cerebral edema 59.…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish resident microglia and blood‐derived macrophages in ischemic brain injury, several studies have been performed using transplanted bone marrow cells from a mouse ubiquitously expressing GFP under the control of a beta‐actin promoter after depleting the intrinsic monocyte population by irradiation (Schilling et al, 2003; Tanaka et al, 2003). A disadvantage with this approach is the possibility that the irradiation used to deplete the endogenous bone marrow may affect the BBB and augment cell infiltration (Hanisch and Kettenmann, 2007). To circumvent this, a recent report employed cranium‐shielded irradiation in bone marrow chimera experiments when addressing the role of blood‐derived macrophages in ischemic stroke, concluding that blood‐derived macrophages recruited via Ccr2 are essential for maintaining integrity of the neurovascular unit following brain ischemia (Gliem et al, 2012), at least in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this, a recent report employed cranium‐shielded irradiation in bone marrow chimera experiments when addressing the role of blood‐derived macrophages in ischemic stroke, concluding that blood‐derived macrophages recruited via Ccr2 are essential for maintaining integrity of the neurovascular unit following brain ischemia (Gliem et al, 2012), at least in adult mice. However, Hanisch et al mentioned that myeloid precursors may be artificially mobilized into circulation by transplantation of bone marrow, which is not physiological (Hanisch and Kettenmann, 2007). Dénes et al demonstrated that there were no significant changes in the ischemic brain damage between Cx3cr1 GFP/+ and wild type mice, and Saederup et al showed that monocyte/macrophage recruitment after thioglycollate‐induced peritonitis was not significantly changed between Cx3cr1 GFP/+ Ccr2 RFP/+ and wild type mice (Dénes et al, 2008; Saederup et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia “at rest” are highly dynamic cells, constantly extending and retracting their processes to sample the local environment via a variety of receptors, including pattern recognition, purinergic, and scavenger receptors (Hanisch & Kettenmann, 2007; Nimmerjahn, Kirchhoff, & Helmchen, 2005). In addition to their immunocompetency, studies implicate microglia in maintaining tissue homeostasis and synaptic connectivity (Kettenmann, Kirchhoff, & Verkhratsky, 2013).…”
Section: Introductionmentioning
confidence: 99%